2017
DOI: 10.1186/s13756-017-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of organ-space surgical site infections after elective colon and rectal surgery

Abstract: BackgroundOrgan-space surgical site infections (SSI) are the most serious and costly infections after colorectal surgery. Most previous studies of risk factors for SSI have analysed colon and rectal procedures together. The aim of the study was to determine whether colon and rectal procedures have different risk factors and outcomes for organ-space SSI.MethodsA multicentre observational prospective cohort study of adults undergoing elective colon and rectal procedures at 10 Spanish hospitals from 2011 to 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
4
34
6
2
Order By: Relevance
“…They might be selected on the basis of indications for operation, and surgeons might also tend to avoid invasive techniques in treating older individuals. ASA score has been confirmed as an independent risk factor of SSI in a few studies [6,16,35], but this association could not be detected in some other surveys [5,18,19,36]. The present data indicated the ASA score more than 2 was a predictive factor in SSI in CRS by the univariate analysis, whereas, not confirmed in the multivariate analysis.…”
Section: Prevalence Of Ssi and Trends Over Timecontrasting
confidence: 83%
See 4 more Smart Citations
“…They might be selected on the basis of indications for operation, and surgeons might also tend to avoid invasive techniques in treating older individuals. ASA score has been confirmed as an independent risk factor of SSI in a few studies [6,16,35], but this association could not be detected in some other surveys [5,18,19,36]. The present data indicated the ASA score more than 2 was a predictive factor in SSI in CRS by the univariate analysis, whereas, not confirmed in the multivariate analysis.…”
Section: Prevalence Of Ssi and Trends Over Timecontrasting
confidence: 83%
“…Besides, longer preoperative hospital stay may also increase patients' risks in developing SSIs by contacting with medical environment or personnel and colonization by microorganisms [34]. Some studies reported that emergent operation was associated with higher rate of SSI after CRS [6,36], and longer surgery duration was an independent risk factor for development of SSI in CRS [16,19,36]. Nevertheless, neither of these factors were confirmed in our data, despite that increasing susceptibility of SSI was detected, whereas, not statistically significant.…”
Section: Prevalence Of Ssi and Trends Over Timecontrasting
confidence: 65%
See 3 more Smart Citations